2016
DOI: 10.1136/postgradmedj-2016-133984
|View full text |Cite
|
Sign up to set email alerts
|

Is there a role for the use of aviation assessment instruments in surgical training preparation? A feasibility study

Abstract: Final year medical trainees from one medical school were able to complete aviation's sensorimotor skills and personality traits selection instruments within the set time frame. They scored differently from aviation trainees on selected skills and personality traits. The applicability and utility of aviation instruments to presurgical training preparation remains to be tested.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 28 publications
(38 reference statements)
0
6
0
Order By: Relevance
“…Theme Three: VSA aptitude testing Twenty-four articles discussed VSA aptitude testing for entry into surgical programs (Table S4). Stolk-Vos and colleagues 86 explored the feasibility of aptitude testing of medical trainees using the Computerized Pilot Aptitude and Screening System (COMPASS). While testing of surgical candidates was deemed feasible, it is unknown whether the COMPASS can predict surgical performance.…”
Section: Theme One: Vsa and Surgical Performancementioning
confidence: 99%
See 1 more Smart Citation
“…Theme Three: VSA aptitude testing Twenty-four articles discussed VSA aptitude testing for entry into surgical programs (Table S4). Stolk-Vos and colleagues 86 explored the feasibility of aptitude testing of medical trainees using the Computerized Pilot Aptitude and Screening System (COMPASS). While testing of surgical candidates was deemed feasible, it is unknown whether the COMPASS can predict surgical performance.…”
Section: Theme One: Vsa and Surgical Performancementioning
confidence: 99%
“…While testing of surgical candidates was deemed feasible, it is unknown whether the COMPASS can predict surgical performance. 86 A systematic review by Maan et al 18 concluded that intermediate-and high-level VSA, specifically on measures of perception, can predict surgical skill acquisition and ability. As such, Maan et al 18 suggested that VSA be used to assess candidates for surgical programs.…”
Section: Theme One: Vsa and Surgical Performancementioning
confidence: 99%
“…The academic results and theoretic paper tests are evaluated for medical students who want to become surgeons without evaluating technical and non-technical abilities, whereas, in case of candidate pilots, they are expected to undergo some personality and sensorimotor tests to check their aptitude before getting admission in a flight school. 11…”
Section: Introductionmentioning
confidence: 99%
“…10 Surgeons, as well as pilots, perform critical functions in a high-risk situation, in a specific well-defined environment and with the use of technology. 11 In spite of these similarities, the selection process for surgeons and pilots is completely different. The academic results and theoretic paper tests are evaluated for medical students who want to become surgeons without evaluating technical and nontechnical abilities, whereas, in case of candidate pilots, they are expected to undergo some personality and sensorimotor tests to check their aptitude before getting admission in a flight school.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation